Strategi Perencanaan dan Rekrutmen SDM di KFC - Rista Aulia; Hendra Riofita (STIKes Ibnu Sina Ajibarang, 2024)
In a rapidly changing and competitive business era, an effective human resource (HR) management strategy is a vital foundation for the sustainable growth of an organization. Basuki expressed this by stating that in a dynamic and competitive business environment, an effective HR strategy is an important key to sustainable growth. This research method is a literature review research. Literature review is a description of theories, findings, and other research materials obtained from reference materials to be used as a basis for research activities to compile a clear framework of thinking from the formulation of the problem to be studied. The author summarizes, analyzes, and synthesizes critically and in depth from previous literature. The results of this study state that Kentucky Fried Chicken (KFC) is one of the largest fast food restaurant chains in the world that focuses on fried chicken. KFC's operational success depends not only on quality products, but also on skilled, motivated human resources (HR) who are in accordance with the organizational culture. In a highly competitive business context, strategic planning and HR recruitment at KFC are one of the main keys to maintaining competitive advantage and the best service to customers.